2009
DOI: 10.1245/s10434-009-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Hypoxia Inducible Factor 1-α and the Impact on the Prognosis of Early Stages of Oral Cancer

Abstract: Our results suggest that G1790A polymorphism in the HIF-1alpha gene might confer susceptibility to OSCC and could be a marker of disfavorable prognosis at early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 26 publications
2
48
1
Order By: Relevance
“…Nevertheless, it has been demonstrated that an invasive grade of breast cancer was negatively correlated to ER and PR expression (23,31,32), but positively correlated with HER2 expression (33,34). Similar to MunozGuerra et al (22) and Lanigan et al (24), we found that the absolute increased gene expression level of CLDN16 was significantly negatively correlated with estrogen and progesterone receptor staining density. However, a significantly positive correlation between absolute increased HAPLN3 and human epidermal receptor 2 staining density, and an insignificant association between overall survival and both gene expression levels were found.…”
Section: ------------------------------------------------------------supporting
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, it has been demonstrated that an invasive grade of breast cancer was negatively correlated to ER and PR expression (23,31,32), but positively correlated with HER2 expression (33,34). Similar to MunozGuerra et al (22) and Lanigan et al (24), we found that the absolute increased gene expression level of CLDN16 was significantly negatively correlated with estrogen and progesterone receptor staining density. However, a significantly positive correlation between absolute increased HAPLN3 and human epidermal receptor 2 staining density, and an insignificant association between overall survival and both gene expression levels were found.…”
Section: ------------------------------------------------------------supporting
confidence: 86%
“…Recently, it has been hypothesized to play a role in carcinogenesis (17,18,22). For breast epithelial cells, the role of the claudin family on breast cancer is still equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…30 Some studies emphasized that G1790A may be a marker of disfavorable prognosis in early stages of oral cancer. 31 We studied rs779805 polymorphism in 5'UTR of VHL gene but no significant differences in genotype and allele frequencies were observed between patients and controls (p> 0.05). Chen et al observed that the rs779805 A>G polymorphism was significantly associated with risk for prostate cancer.…”
Section: Discussionmentioning
confidence: 91%
“…Overall,26 relevant studies involving 6337 cases and 9302 controls were selected in this metaanalysis [21,26,27,29,30,32,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. The main characteristics of these studies were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A number of investigators have studied the possible association between the Hif-1/HIF-1 polymorphisms and cancer risk, but the results have been conflicting [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Thus, the association between the Hif-1/HIF-1 polymorphisms and cancers requires further investigation.…”
mentioning
confidence: 99%